2012
DOI: 10.11124/jbisrir-2012-19
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Facilitators and Barriers to Interventions Aimed at Reducing Unintended Pregnancies among Adolescents in Low and Middle Income (Developing) Countries: a Systematic Review of Qualitative Evidence

Abstract: IMPLICATIONS FOR RESEARCH: Further research should be conducted into the following.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 43 publications
0
6
1
Order By: Relevance
“…The fear of perceived complications from FP use [14]- [16] [18] could prevent adolescents from accessing such services. Another relevant finding from this study was cost of services that did come up as a barrier in this study in contrast to an earlier review of experiences of young persons from LMICs [19].…”
Section: Discussioncontrasting
confidence: 62%
“…The fear of perceived complications from FP use [14]- [16] [18] could prevent adolescents from accessing such services. Another relevant finding from this study was cost of services that did come up as a barrier in this study in contrast to an earlier review of experiences of young persons from LMICs [19].…”
Section: Discussioncontrasting
confidence: 62%
“…Females' contraceptive patronage was lower than that of males at their last sexual encounter. Possible reasons for this situation could be the fear of perceived complications from contraceptive use, and stigmatization from society and health workers [23] [24] The study observed that the male condom and withdrawal were popular and common to both sexes. Another interesting observation by the study was that females would have preferred using the pill and injectable in the future, in direct contrast to their current use of the methods.…”
Section: Discussionmentioning
confidence: 99%
“…19 In Ghana, as in most LMICs, gender inequality was also mediated through social norms that subordinate adolescent girls to men and limits their ability to make independent SRH decisions. 6 Gender inequality was also reinforced by family poverty, a phenomenon that led some parents to force their daughters into early marriage while others encouraged their daughters to engage in sex for money to support the family. Family poverty has been shown to exacerbate gender inequalities in other LMICs.…”
Section: Discussionmentioning
confidence: 99%
“…As in Ghana, a deeply embedded sense of disapproval of adolescent sexual activity has been reported in other LMICs. 6 27 Conversely, some community members and adolescent girls themselves stigmatised late childbearing as a sign of infertility. The stigma of late childbearing was thought to create an environment which influenced some adolescent girls to engage in sexual activity despite prohibitionary social norms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation